5B.001 Developing behavioural theory grounded and user-centred mobile app to prevent infant falls. (14th March 2021) - Cooray, Nipuna; Sun, Si; Adams, Susan; Elkington, Jane; Ho, Catherine; Keay, Lisa; Nassar, Natasha; Brown, Julie
Abstract : Background: Digital behaviour change interventions (DBCI) are common public health tools but their use in injury prevention is limited. This paper presents the development and user-testing of the first module to be implemented in a mobile app designed as a DBCI to prevent infants falls. Methods: We used the Behaviour Change Wheel (BCW) to guide DBCI development, and review of literature and parental forum discussions to identify target behaviours. These were mapped to Behaviour Change Techniques (BCTs) and a logic model was constructed. For pilot-testing, pregnant mothers were provided the app to review. Feedback through think-a-loud interviews and an iterative process of user-testing was used to refine the app until comprehension criteria was reached: 80% of participants achieving ≥90% correct comprehension. Results: Development work identified key target behaviours, including mother getting adequate rest, safe feeding practices and safe infant placing after a feed. BCTs identified were information on health consequences, credible information, social support, prompts and cues, instruction and self-monitoring. For pilot-testing, 20 pregnant mothers were recruited, and 4 iterations of app refinement were required to reach the comprehension target. Acceptability was high and logic model changes were minimal. Discussion and Conclusion : This project demonstrates our novel development pathway and likely acceptance of the DBCI but further work is required to examine app engagement. Once fully implemented, the impact on behaviour change will be examined. Learning Outcomes: Use of the BCW and a user-centred approach is a feasible method for development of DBCI for injury prevention.